Produção e caracterização de carvões de eucaliptos ativados fisicamente com co2 ou gás da carbonização - Nubia Rangel Candido (2018)
Activated carbons (AC) are materials with high adsorptive capacity used in a wide range of industrial applications, with emphasis to environmental recovery and purification. Worldwide, water treatment accounts for the largest share of consumption of these materials (41%). The most commonly used method for industrial production of AC is through physical activation, since it does not require chemical products. The process consists of two stages: in the first one, called carbonization, in addition to a solid material, liquid products (pyroligneous acid and wood tar) and non-condensable gases like CO2, CO, H2O, CH4, H2 are also produced; in the second stage, the solid obtained is gasified by a partially oxidizing atmosphere (usually water vapor or CO2) in a temperature range from 700 to 950 °C. Regarding that, for lignocellulosic precursors, the main activating agents used in the second stage are generated during the first one, the main objective of this project was to produce AC of eucalyptus wood, for application into water treatment, using the gas generated during carbonization of the precursor in an industrial furnace as activating agent. Initially, it was studied the conventional activation with pure CO2, for future comparison with the AC produced using the carbonization gas. AC obtained with the carbonization gas presented similar structures to those activated with pure CO2, being mostly microporous, although they demanded a bigger weight loss due to the presence of O2 in the carbonization gas composition. The temperature of 850 ºC was identified as the optimal temperature for both activating agents. The sample activated with carbonization gas at 850 ºC, with 49% of weight loss, presented BET surface area of 680 m2 g -1 , V0.95 of 0.316 cm3 g -1 , Vmic of 0.276 cm3 g -1 , iodine number of 643 mg g-1 and the phenol index of 2.0 g L-1 , while the pure CO2 activated sample with 33% of weight loss presented a BET surface area of 695 m2 g -1 , V0.95 of 0.303 cm3 g -1 , Vmic of 0.277 cm3 g -1 , iodine number of 672 mg g-1 , and phenol index of 2.2 g L-1 . Both samples met the specifications of NBR 11834 standards for application of activated carbon in water treatment. Results showed that the proposed methodology for the use of the gas generated during the carbonization presents great potential for industrial production of activated carbon